Compare the axial bearing capacity piles cylindrical, tapered and semi-tapered in the sand by finite element method - واحد قیاسی (Iranian Society of Structrual Engineering (ISSE), 2019)
Use piles with variable section can improve the bearing capacity of the piles, due to the larger cross-section upper part of piles. The function and easy implementation of semi-tapered piles that only the top half is in the form of a cone are better than the previous one. The purpose of this paper is determine the bearing capacity increase tapered and semi-tapered tapered piles and comparing with the cylindrical piles in the same volume condition. The modeling of this research paper is based on finite element method (Plaxis 2D software) of numerical analysis for changing the angle and tapered height of mentioned piles, axial bearing capacity of these piles in sand is estimated. Linear elastic behavior is assumed for pile and the hardening soil criterion is considered for soil. The analysis was performed for piles with different lengths. Load carrying capacity and settlement at the given particular loading were examined. Influences of stresses are also discussed with respect to change in taper angle. The results show that settlement decreases with increase in taper angle. Load-displacement curve shows that the tapered pile can take more loads compared to cylindrical pile when the taper angle load- settlement curve of piles compare showed that tapered piles bearing capacity and especially semi-tapered piles greater than cylindrical piles. It was also observed that the increase in capacity, more piles occur with short length.